RECONSTRUCTION OF THE CONTENTS OF INDONESIAN ADVOCATE’S CODE OF ETHICS IN THE PERSPECTIVE OF ISLAMIC LAW - Almahdi Akbar; Gunarto; Ahmad Khisni (Journal of Islamic, Social, Economics and Development, 2020)
The finding confirms that there are several articles in the Advocate's code of ethics have a contrary character to ethics and religious values. This study aims to (1) examine and analyze the Indonesian lawyers' code of ethics which is not reflect perspective on Islamic law; (2) review and analyze the weaknesses of the contents of the current Indonesian advocate code of ethics, and (3) reconstruct the contents of the Indonesian lawyers' code of ethics in the perspective of Islamic law. The research approach used was normative juridical approach to legislation (statute approach), and conceptual approach (conceptual approach). Data sources consist of primary data such as Law Number 18 Year 2003 Indonesian Advocates Code of Ethics. Secondary law books include Fiqh literature. Data collection techniques include library research techniques. The analysis technique used was qualitative descriptive analysis with inductive and deductive methods. The results of this study found that the first Indonesian advocate’s code of ethics has not reflect Islamic law perspective in the provisions of Article 2. The Indonesian Advocates Code of Ethics laid down the taqwa criteria on advocate personalities, but did not mention the taqwa criteria when carrying out advocate duties, then in the provisions of article 4 Indonesian Advocates (ILCE) give absolute freedom to advocates in terms of holding secret positions to their clients; The two weaknesses of the Indonesian advocate's code of ethics are found in the substance, culture and legal structure. The three reconstructions carried out in the Indonesian advocate's code of ethics are to incorporate moral values in accordance with Islamic law in articles that have no Islamic law perspective. Recommendations/suggestions in this study: First, advocate organizations are expected to change the advocates’ code of ethics to be devoted and hold on to religious values, and maintain client secrets to realize legal ideals. Second, it is expected that the Government, Legislative and Advocate Organizations will commit to create moral advocates. Third, in the advocacy of advocates not only focus on special education materials for advocate professions. An advocate's exam is not just about answering questions. But by conducting a process of investigation of the behavior of the prospective advocate when the two-year internship that he lived.